2007
DOI: 10.1002/arch.20187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octopamine on reproduction, juvenile hormone metabolism, dopamine, and 20‐hydroxyecdysone contents in Drosophila

Abstract: The effect of an experimentally increased octopamine content (feeding flies with OA) on the levels of juvenile hormone (JH) degradation, dopamine (DA), and 20-hydroxyecdysone (20E) contents, oogenesis, and fecundity of wild type Drosophila flies has been studied. OA feeding of the flies was found to (1) cause a considerable decrease in JH degradation in females, but not males, of D. melanogaster and D. virilis; (2) have no effect on DA content in D. melanogaster and D. virilis; (3) increase 20E contents in D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 37 publications
3
27
0
2
Order By: Relevance
“…aegypti and Drosophila. In agreement with our observation of Drosophila larvae, Gruntenko et al [15] showed that an increased level of octopamine was related to a decreased number of vitellogenic (stages 8-10) and mature (stage 14) oocytes in Drosophila virilis as well as a decreased fecundity of D. melanogaster and D. virilis. Our observation that exposure to formamidine suppresses insect feeding is supported by a large body of evidence.…”
Section: Discussionsupporting
confidence: 90%
“…aegypti and Drosophila. In agreement with our observation of Drosophila larvae, Gruntenko et al [15] showed that an increased level of octopamine was related to a decreased number of vitellogenic (stages 8-10) and mature (stage 14) oocytes in Drosophila virilis as well as a decreased fecundity of D. melanogaster and D. virilis. Our observation that exposure to formamidine suppresses insect feeding is supported by a large body of evidence.…”
Section: Discussionsupporting
confidence: 90%
“…Three hormones interrelated by their canonical roles in morphogenesis are shown here to maintain their relationship despite dramatic reorganization of the body plan following metamorphosis. The diversity of allato-regulators in Drosophila, including insulin-like peptides and biogenic amines (40)(41)(42)(43), also influence JH production; each may influence this network in a context-specific manner to coordinate and optimize reproductive behaviors. The ability of the CA to integrate a variety of inputs, including nutrition and steroid levels, into a proreproductive signal bears a striking similarity to the mammalian GnRH neuron, which integrates complex hormonal information regarding stress, nutrition, and circadian rhythm into its activity, the emergent hormonal state determining whether reproduction is appropriate (44).…”
Section: Discussionmentioning
confidence: 99%
“…Octopamine may also act as a neurohormone in controlling the metabolism of gonadotropins (juvenile hormone and 20-H ecdysone; Gruntenko et al 2007). dVMAT mutants show an eggretention phenotype similar to mutants with reduced octopamineric signaling.…”
Section: Discussionmentioning
confidence: 99%